The Munich Coma Scle (MCS). Issue 8 (August 1976) - Brinkmann, R; Von Cramon, D; Schulz, H
Abstract : The level of coma can be measured by the assessment of changes of behaviour after different intensities of stimulation. Two additive scales (Guttman scales) for susceptibility to stimulation and reactivity were developed, constituting the Munich Coma Scale (MCS). The findings of previous investigations were repeated in a new sample of 67 comatose patients. Implications of the additivity of reactivity are discussed and related to the concept of 'behavioural arousal' advanced in the recent literature.